Gender Differences in the Score and Influencing Factors of Social Participation among Chinese Elderly. (4th July 2022) - Yuying, Zhong; Jing, Cheng
ABSTRACT: This study measured the social participation score of the Chinese elderly, described its decayed trajectory based on birth cohort, and analyzed the gender differences of factors that affected the social participation of the elderly based on MIMIC model by groups. Results showed that age, economic status, and living status were the influencing factors with significant gender differences on social participation level of Chinese elderly. At any age, the social participation of Chinese elderly women was lower than that of elderly men, and this gap widened with age. Social participation of older women was more vulnerable to economic conditions. Living with children had a significant negative impact on the social participation of elderly women. There was no significant gender difference in the influence of marital status and educational level on the social participation of the elderly.